On the type material of Palearctic species of Drosophilidae (Diptera). - Bächli, Gerhard (Beiträge zur Entomologie = Contributions to Entomology, 1982)
Für alle vor 1956 beschriebenen palearktischen Drosophilidae-Arten ist das Typenmaterial, sein Aufbewahrungsort und seine Bezettelung aufgelistet. Lectotypen sind festgelegt, soweit das zweckmäßig ist. Nomenklatorische Handlungenformosus (Loew, 1864) (Acletoxenus), Lectotype described as Gitona formosusindagator Loew, 1858 (Cacoxenus), Lectotypeperspicax (Knab, 1914) (Cacoxenus), Lectotype described as Gitonides perspicaxdistincta (Egger, 1862) (Chymomyza), Lectotype described as Drosophilaobscura (de Meijere, 1911) (Chymomyza), Lectotype described as Amphoroneura obscuraoldenbergi Duda, 1934 (Chymomyza), Lectotypepictipes (de Meijere, 1911) (Dettopsomyia), Lectotype described as Drosophila pictipesadspersa Mik, 1886 (Drosophila), Lectotypealboralis Momma & Takada, 1954 (Drosophila), Lectotypeapproximata Zetterstedt, 1847 (Drosophila), Lectotypebusckii Coquillett, 1901 (Drosophila), Lectotypecameraria Haliday, 1833 (Drosophila), Lectotypecinerella Fallén, 1823 (Drosophila), Lectotypefasciata Meigen, 1820 (Drosophila), Lectotypefenestrarum Fallén, 1823 (Drosophila), Lectotypegrischuna Burla, 1951 (Drosophila), Lectotypekuntzei Duda, 1924 (Drosophila), Lectotypelaeta Zetterstedt, 1847 (Drosophila), Lectotypelatestriata Becker, 1908 (Drosophila), Lectotypelimbata van Roser, 1840 (Drosophila), Lectotypeobscura Fallén, 1823 (Drosophila), Lectotypeoldenbergi Duda, 1924 (Drosophila), Lectotypephalerata Meigen, 1830 (Drosophila), Lectotypepilosula Becker, 1908 (Drosophila), Lectotypeprorepleta Duda, 1925 (Drosophila), Lectotyperubrostriata Becker, 1908 (Drosophila), Lectotyperuficeps von Roser, 1840 (Drosophila), Lectotyperufifrons Loew, 1873 (Drosophila), Lectotypeschmidti Duda, 1924 (Drosophila), Lectotypetestacea von Roser, 1840 (Drosophila), Lectotypetransversa Fallén, 1823 (Drosophila), Lectotypetsigana Burla & Gloor, 1952 (Drosophila), Lectotypeuvarum Rondani, 1875 (Drosophila), Lectotypeversicolor Mather, 1955 (Drosophila), Lectotypevirginea Meigen, 1830 (Drosophila), Lectotypebeckeri (Duda, 1924) (Gitona), Lectotype described as drosophila beckeriinterrupta Duda, 1924 (Leucophenga), Lectotypequadripunctata (de Meijere, 1908) (Leucophenga), Lectotype described as Drosophila quadripunctatasubpollinosa (de Meijere, 1914) (Leucophenga), Lectotype described as Drosophila subpollinosanitida Duda, 1922 (Liodrosophila), Lectotypecongesta (Zetterstedt, 1847) (Microdrosophila), Lectotype described as Drosophila congestanigriventris (Zetterstedt, 1847) (Microdrosophila), Lectotype described as Drosophila nigriventrisgratiosa (de Meijere, 1911) (Mycodrosophila), Lectotype described as Drosophila gratiosaamoena (Meigen, 1838) (Scaptomyza), Lectotype described as Hydrellia amoenadisticha (Duda, 1921) (Scaptomyza), Lectotype described as Drosophila distichaflavipennis (Zetterstedt, 1838) (Scaptomyza), Lectotype described as Drosophila flavipennisgraminum (Fallén, 1823) (Scaptomyza), Lectotype described as Drosophila graminumimpunctata (Frey, 1945) (Scaptomyza), Lectotype described as Scaptomyzella impunctataincana (Meigen, 1830) (Scaptomyza), Lectotype described as Drosophila incanapallida (Zetterstedt, 1847) (Scaptomyza), Lectotype described as Drosophila pallidarufipes (Meigen, 1830) (Scaptomyza), Lectotype described as Drosophila rufipessordida (Zetterstedt, 1838) (Scaptomyza), Lectotype described as Drosophila sordidacurvipennis (Fallén, 1823) (Stegana), Lectotype described as Drosophila curvipennisfurta (Linnaeus, 1766) (Stegana), Lectotype described as Musca furtanigrifrons (de Meijere, 1911) (Stegana), Lectotype